2013
DOI: 10.3163/1536-5050.101.3.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of library instruction: do first-year medical students use library resources specifically highlighted during instructional sessions?

Abstract: Students cited resources specifically highlighted during library instructional sessions for their assignments. The percentage of all citations coming from resources highlighted during the instructional sessions or found on the course LibGuide indicates that library instruction had an impact on the students' work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
4
13
0
Order By: Relevance
“…To date, several studies report that one-off workshops, tailored to the needs of student groups, may result in the increased use of specific databases (Rafferty, 2013;Van Epps, 2013). Similar to the results of this article, these studies found that the educational interventions used had a positive impact on student assignments.…”
Section: Commentarysupporting
confidence: 79%
“…To date, several studies report that one-off workshops, tailored to the needs of student groups, may result in the increased use of specific databases (Rafferty, 2013;Van Epps, 2013). Similar to the results of this article, these studies found that the educational interventions used had a positive impact on student assignments.…”
Section: Commentarysupporting
confidence: 79%
“…Effects associated with librarian-led trainings in literature searching for medical students can include increased confidence and use of demonstrated resources (Miller, 2014;Rafferty, 2013). However, some studies offer conflicting findings.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Through analysis of students' annotated bibliographies, the study revealed student strengths in locating sources and weaknesses in evaluating source credibility (p. 49), and informed modifications to libraryinstruction practice. In a more basic application of citation analysis, Rafferty (2013) determined that first-year medical students consistently adhered to source material previously introduced in library instruction sessions (p. 216). Applying a citation analysis rubric in the form of a checklist corresponding to ACRL standards, Rosenblatt (2010) found that students were generally able to locate appropriate material for a research topic but demonstrated a lack of ability to critically discern and incorporate found sources into their work (p. 60).…”
Section: Literature Reviewmentioning
confidence: 99%